Using Logistic Regression to Model New York City Restaurant Grades Over a Two-Year Period (Epidemiology, Biostatistics, and Public Health, 2022)
A knowledge gap exists in the role of restaurant type on the prediction of attaining the highest grade possible from the local health inspection agency. This study identified disparities using logistic regression between the issuance of a Grade A and restaurant type and location. This study tested the eight most inspected types of restaurants within the City of New York and calculated the odds ratios of their receiving the highest inspection grade by the New York City Department of Health and Mental Hygiene. A fitted equation has been proposed for the prediction of receiving the highest inspection grade based upon the citywide results of these eight restaurant types from calendar years 2011 and 2012. The results suggest that certain styles of restaurants have lower odds of receiving the highest grade in comparison to American-style restaurants
Keywords: Restaurants; Public Health; Inspections; Regression